A tiny but crucial player bridging microbes and colonic carcinogenesis - Otsuka, Motoyuki; Ishibashi, Rei; Tanaka, Eri; Seimiya, Takahiro; Suzuki, Tatsunori; Sekiba, Kazuma; Yamagami, Mari; Ohno, Motoko; Kishikawa, Takahiro; Koike, Kazuhiko (Translational Cancer Research, 2017)
Colorectal cancer (CRC) is one of the most common malignancies in the world (1). The probability of suffering from CRC is approximately 4–5%, and the risk of developing CRC is associated with characteristics such as age, chronic disease history, and lifestyle (2). CRC is caused by mutations in oncogenes, tumor-suppressor genes, and genes related to DNA repair mechanisms. The underlying pathogenic mechanisms are threefold; namely, chromosomal instability (CIN), microsatellite instability (MSI), and CpG island methylator phenotype (CIMP). In CRC, common mutations, chromosomal changes, and translocations reportedly affect important intracellular signaling pathways [WNT, mitogen activated protein kinase (MAPK)/phosphoinositide 3-kinase (PI3K), transforming growth factor (TGF)-β, and TP53] (2). In addition to genetic mutations, alterations in non-coding RNAs, such as microRNAs, also contribute to carcinogenesis.